Potential Drug–Drug Interactions in Antihypertensive Therapy Among Outpatients with Comorbidities: Prevalence, Severity, and Clinical Implications - Prita Anggraini Kartika Sari; Rahayu, Ade Rahmawati; Noor Faridah, Imaniar; Supadmi, Woro; Sari, Andriana; Ahmed, Bilal (Universitas Ahmad Dahlan, 2026)
Hypertension is a condition that frequently coexists with comorbidities, often necessitating polypharmacy and consequently increasing the risk of drug-drug interactions (DDIs). This study aimed to analyze the pattern and severity of potential DDIs among hypertensive outpatients with comorbidities at North Lombok Regional General Hospital in 2024. This study employed a descriptive observational design with retrospective data collection. A total of 100 outpatient medical records meeting the criteria were selected via probability sampling from the hospital database during January to December 2024. Among the included patients, 50% were aged >60 years, 60% were female, and 91% were covered by the National Health Insurance. Potential DDIs were assessed using the Drugs.com drug interaction checker and categorized based on severity into major, moderate, and minor. A total of 257 potential DDI events were identified, consisting of 19 major interactions (7.4%), 205 moderate interactions (79.8%), and 33 minor interactions (12.8%). The most frequent major interaction was the combination of spironolactone and candesartan, which poses a significant risk of hyperkalemia and hypotension. Moderate interactions were predominantly observed with the combination of furosemide and bisoprolol, which may increase the risk of hyperglycemia and hypertriglyceridemia. Meanwhile, the most frequent minor interaction was aspirin with bisoprolol, which may reduced beta-blocker antihypertensive effect. In conclusion, this study found that moderate severity potential DDIs were the most prevalent and could significantly impact therapeutic outcomes in hypertensive patients with comorbidities. These findings highlight the critical role of clinical pharmacists in identifying and mitigating clinically significant interactions through rigorous prescription monitoring, patient education, and optimization of drug therapy. Strengthened monitoring and evaluation of drug regimens are recommended to minimize the risk of adverse drug reactions and enhance patient safety.